Death penalty in decline?: the fight against capital punishment in the decades since Furman v. Georgia - Sarat, Austin (Temple University Press, 2024)
"This volume presents essays evaluating the similarities and differences between the legal, political, ethical, and practical landscapes confronted by the death penalty abolition movement at the time of the Furman v. Georgia decision and subsequent reversal and those confronted by the same movement today"--